Music therapy modulates mothers’ perception of their preterm infants - Kobus, Susann; Diezel, Marlis; Dewan, Monia Vanessa; Huening, Britta; Dathe, Anne-Kathrin; Marschik, Peter B.; Felderhoff-Mueser, Ursula; Bruns, Nora (Frontiers in Psychology, 2023)
Premature birth imposes considerable challenges on the preterm infant, but also challenges the mother, who may not yet be prepared for motherhood and encounter psychological stress during the post-partum period. This secondary analysis of a prospective randomized controlled trial (RCT) aimed to investigate how mothers perceive their preterm infants. We surveyed thirty-three mothers of preterm infants born before 32 weeks of gestation, who were participating in an RCT on music therapy. We employed the neonatal perception inventory (NPI), an instrument designed to assess the mother’s perception and expectations regarding her infant immediately after birth. Infants were randomly assigned to either standard care (control group) or standard care plus music therapy (intervention group). Eighteen mothers from the intervention group participated in the survey (mean age 34.1 ± 4.6 years) and 15 mothers from the control group (mean age 29.6 ± 4.2). At the time of the infant’s hospital discharge, mothers rated their expectations of how they felt a baby should behave (NPI I) and how they perceived their own infant (NPI II). The NPI score difference was calculated by subtracting the NPI II from the NPI I. Mean NPI I scores were comparable between both groups, but NPI II scores in the intervention group were better (18.0, 95% confidence interval (CI) 16.6 – 19.4) than in the control group (19.1, 95% CI 18.0 – 20.3). The relative probability of mothers rating their own baby as better than average was 1.94 (95 % CI 1.00 – 3.79) for mothers whose infants received music therapy. These findings suggest that music therapy in the neonatal intensive care unit can positively influence mothers’ perception of their hospitalized preterm infant.